Surface Protein IsdC and Sortase B Are Required for Heme-Iron Scavenging of Bacillus anthracis - Maresso, Anthony W. (American Society for Microbiology, 2006)
Bacillus anthracis, the spore-forming agent of anthrax, requires iron for growth and is capable of scavenging heme-iron during infection. We show here that the B. anthracis iron-regulated surface determinants (isd) locus encompasses isdC, specifying a heme-iron binding surface protein. Anchoring of IsdC to the cell wall envelopes of vegetative bacilli requires srtB, which encodes sortase B. Purified sortase B cleaves IsdC between the threonine and the glycine of its NPKTG motif sorting signal. B. anthracis variants lacking either isdC or srtB display defects in heme-iron scavenging, suggesting that IsdC binding to heme-iron in the cell wall envelope contributes to bacterial uptake of heme.